Phosphorylation potential of Drosophila E-Cadherin intracellular domain is essential for development and adherens junction biosynthetic dynamics regulation. - Chen, Y.J.; Huang, J.; Huang, L.; Austin, E.; Hong, Y. (Development, 2017)
Phosphorylation of a highly conserved serine cluster in the intracellular domain of E-Cadherin is essential for binding to ?-Catenin in vitro In cultured cells, phosphorylation of specific serine residues within the cluster is also required for regulation of adherens junction (AJ) stability and dynamics. However, much less is known about how such phosphorylation of E-Cadherin regulates AJ formation and dynamics in vivo In this report, we generated an extensive array of Drosophila E-Cadherin (DE-Cad) endogenous knock-in alleles that carry mutations targeting this highly conserved serine cluster. Analyses of these mutations suggest that the overall phosphorylation potential, rather than the potential site-specific phosphorylation, of the serine cluster enhances the recruitment of ?-Catenin by DE-Cad in vivo Moreover, phosphorylation potential of the serine cluster only moderately increases the level of ?-Catenin in AJs and is in fact dispensable for AJ formation in vivo Nonetheless, phosphorylation-dependent recruitment of ?-Catenin is essential for development, probably by enhancing the interactions between DE-Cad and ?-Catenin. In addition, several phospho-mutations dramatically reduced the biosynthetic turnover rate of DE-Cad during apical-basal polarization, and such biosynthetically stable DE-Cad mutants specifically rescued the polarity defects in embryonic epithelia lacking the polarity proteins Stardust and Crumbs.